Exceptional Long-term Response to Immunotherapy in an African American Man With -Mutated Metastatic Lung Adenocarcinoma - Yaolin Zhou; Maneesh Gaddam; Sunil Badami (Journal of Investigative Medicine High Impact Case Reports)
Immunotherapy has become the standard of care for advanced and resectable lung cancer, and specific mutations may predict immunotherapy response. For example, STK11 mutations, which are more common in African American patients, are associated with immunotherapy resistance. A 68-year-old African American man with stage IIIB lung adenocarcinoma with mediastinal lymph node involvement progressed on first-line concurrent carboplatin-based chemoradiotherapy. Molecular testing of the patient’s subcarinal lymph node tissue revealed STK11 S216F, TP53 R273L, and RB1 splice site mutations; high tumor mutation burden (19.0 mutations/Mb); and high PD-L1 22c3 expression (TPS 70%, 2+ intensity). Treatment with carboplatin-based chemotherapy with radiation therapy failed to control the disease, but the patient has tolerated and responded well to intravenous pembrolizumab. Although STK11 mutations are associated with immunotherapy resistance, our patient demonstrated an exceptional and sustained response to immunotherapy for over two years. The patient’s STK11/TP53 co-mutation, along with high TMB and PD-L1 22c3 TPS scores, may help explain his continued responsiveness to immunotherapy and longer survival. Importantly, incorporating genetic ancestry differences in mutation prevalence and the impact of specific mutations and co-mutations, may help ensure the equitable and optimal treatment of all patients with lung cancers.